REPRESENTAÇÕES SOCIAIS E CONSTRUÇÃO DAS DISCURSIVIDADES NO CONTEXTO ESCOLAR: um estudo sobre o fenômeno do Bullying - Botelho, Carolline de Souza (2013)
This essay reflects on the bullying phenomenon, characterized as a specific type of violence that manifests itself from the concrete forms of aggression, to the more subtle forms such as psychological violence also addressed in this research as symbolic violence, in the perspective bourderiana . In the first part of the work, a theoretical analysis of the concept of violence which also approached in general, surveys and studies conducted in Brazil in the late 1970s. In the second part of the research, reflect on the phenomenon of bullying from an analysis based violence in some psychoanalytic theories of Lacan. The relevance of this framework aligned to the objectives of this because it allowed us to think about what the position occupied by the individuals involved in the practice of bullying in the knowledge that guide their movement by social fabric, more specifically, by the school. The course offered here by Lacan (1998) and verified in communication. The mirror stage was crucial since it considers that the subject must be understood from the combination of symbolic systems and sociocultural and offered us the clues to careful observation about discursive network that are established in school spaces, because from the universe empirical analysis, we can understand the dynamics of representations played in the school context and social representations that the students have about bullying. With the split of steps quantitative and qualitative applied to the universe of 427 students from 6th to 8th year in a private school education in São Luis Maranhão, it was concluded that bullying can therefore be seen as a result of the conflict specifications and social discourses involving power relations, where the victims are determined by the fact of belonging to different subgroups defined by age, gender, socioeconomic status, race, ethnicity, religion, etc. We emphasize that this work is within the framework of studies investigating the relationship between culture and education, from social representations and aims to contribute to understanding some of the social dimensions related to maltreatment by exploiting the insights that teenagers and parents are the protagonists in situations of victimization and aggression among peers, peering attitudes to offenders, victims and observers.